1997
DOI: 10.1046/j.1365-2036.1997.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of N‐acetylcysteine are altered in patients with chronic liver disease

Abstract: Background: The threshold plasma paracetamol concentration at which N‐acetylcysteine (NAC) treatment is recommended to treat paracetamol poisoning in a patient with induced liver enzymes (for example, with chronic liver disease or taking anticonvulsant drugs) is 50% lower than in a patient without induced liver enzymes. More patients with chronic liver disease might therefore be expected to be exposed to NAC treatment than previously. In addition, there is increasing use of NAC in patients with chronic liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…The dose employed was fixed at 600 mg twice daily in accordance with the bioavailability of the drug [29]. No Nacetylcysteine adverse effects were found in our study, in contrast with the data reported by Baker et al after the employment of a larger dose and with a different administration rate (RAPPID study) [12].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The dose employed was fixed at 600 mg twice daily in accordance with the bioavailability of the drug [29]. No Nacetylcysteine adverse effects were found in our study, in contrast with the data reported by Baker et al after the employment of a larger dose and with a different administration rate (RAPPID study) [12].…”
Section: Discussioncontrasting
confidence: 56%
“…A low intravenous dose of N-acetylcysteine was employed during the 6 h before the procedure for two different reasons: Firstly, the coronary angiography was considered to be an emergency procedure in our patients, so it made it impossible to administer the drug during the day before, and secondly, due to the metabolite terminal half-life described in previous pharmacokinetic studies [28][29][30].…”
Section: Discussionmentioning
confidence: 98%
“…N-acetylcysteine, on the other hand, acts by replenishing glutathione stores and is likely to be more effective, but it has the disadvantage of reducing tissue extraction of oxygen in cirrhotic patients. 99 A recent study has shown a possible role for SAMe, if given perioperatively, in attenuating reperfusion injury. 98 SAMe is an endogenous methyl group donor, a precursor of adenosine and glutathione.…”
Section: Reperfusionmentioning
confidence: 99%
“…The results can be attributed to direct interaction of NAC with ROS or enhancement of cellular GSH synthesis. On the other hand, NAC has some side effects, including being prooxidant, suppressing respiratory burst, and causing a toxic ammonia accumulation in case of liver problems (Holdiness 1991;Jones et al 1997). More attention should be paid to the selection of the indication and dose of NAC in clinical application.…”
Section: Discussionmentioning
confidence: 99%